Simple simultaneous determination of moxifloxacin and metronidazole in complex biological matrices. Issue 25 (23rd May 2022) - El-Yazbi, Amira F.; Aboukhalil, Faten M.; Khamis, Essam F.; Elkhatib, Mohammed A. W.; El-Sayed, Mahmoud A.; Youssef, Rasha M.
Abstract : A simple, sensitive and rapid RP-HPLC method is presented, for the first time, for the simultaneous determination of moxifloxacin hydrochloride and metronidazole in different biological fluids including saliva and plasma without any matrix interference. Abstract : A simple, sensitive and rapid RP-HPLC method is presented, for the first time, for the simultaneous determination of moxifloxacin hydrochloride and metronidazole in different biological fluids including saliva and plasma without any matrix interference. The separation was performed using ACN and phosphate buffer (30 : 70% v/v) as the mobile phase on a Zorbax Eclipse Plus-C18 column attached to a guard column. The method was validated according to the FDA guidelines for bioanalytical method validation and was successfully applied for simultaneous determination of the studied drugs in saliva and plasma samples. The good precision and selectivity of the developed method allow it to be used for routine therapeutic drug monitoring of such drugs and it presents a simple and sensitive analytical tool for performing versatile pharmacokinetics and bioavailability studies. A DAD detector is valuable to determine each drug at its maximum wavelength to ensure high sensitivity. Determination of such a combination in saliva introduces a quick and non-invasive alternative to blood analysis.